Pengaruh Pengetahuan Informasi Akuntansi Terhadap Kinerja Usaha Mikro, Kecil, dan Menengah - Angelin, Devna Callista; Kusumastuti, Ratih (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
The growth of MSMEs in 2018 reached 64.2 million actors and increased during the COVID-2019 pandemic, knowledge of accounting is very important to be able to monitor and improve business performance for business actors not only large businesses but also MSME owners. This study aims to determine and analyze the effect of accounting information knowledge on the performance of micro, small and medium enterprises (MSMEs) in several MSMEs with qualitative research with a literature study method sourced from five journal articles and one thesis. The results of this study indicate a positive relationship between accounting knowledge and performance improvement in MSMEs.